In Vitro Evaluation of an External Compression Device for Fontan Mechanical Assistance. Issue 3 (22nd October 2013) - Valdovinos, John; Shkolyar, Eugene; Carman, Gregory P.; Levi, Daniel S.
Abstract While Fontan palliation in the form of the total cavopulmonary connection has improved the management of congenital single ventricle physiology, long‐term outcomes for patients with this disease are suboptimal due to the lack of two functional ventricles. Researchers have shown that ventricular assist devices (VADs) can normalize Fontan hemodynamics. To minimize blood contacting surfaces of the VAD, we evaluated the use of an external compression device (C‐Pulse Heart Assist System, Sunshine Heart Inc.) as a Fontan assist device. A mock circulation was developed to mimic the hemodynamics of a hypertensive Fontan circulation in a pediatric patient. The Sunshine C‐Pulse compression cuff was coupled with polymeric valves and a compressible tube to provide nonblood‐contacting pulsatile flow through the Fontan circulation. The effect of the number, one or two, and placement of valves, before or after the compression cuff, on inferior vena cava pressure (IVCP) was studied. In addition, the effect of device inflation volume and compression rate on maintaining low IVCP was investigated. With one valve located before the cuff, the device was unable to maintain an IVCP below 15.5 mm Hg. With two valves, the C‐Pulse was able to maintain IVCP as low as 8.5 mm Hg. The C‐Pulse provided pulsatile flow and pressure through the pulmonary branch of the mock circulation with a pulse pressure of 16 mm Hg and 180 mL/min additional flow above unassisted flow. C‐Pulse compression reduced IVCP below 12 mm Hg with 13 cc inflation volume and compression rates above 105 bpm. This application of an external compression device combined with two valves has potential for use as an artificial right ventricle by maintaining low IVCP and providing pulsatile flow through the lungs.